Temporally and sex-specific effects of maternal perinatal stress on offspring cortical gyrification and mood in young adulthood - Mareckova, Klara; Miles, Amy; Andryskova, Lenka; Brazdil, Milan; Nikolova, Yuliya S (Human brain mapping, 2020)
Maternal stress during pregnancy and shortly thereafter is associated with altered offspring brain development that may increase risk of mood and anxiety disorders. Cortical gyrification is established during the prenatal period and the first 2 years of life and is altered in psychiatric disorders. Here, we sought to characterize the effects of perinatal stress exposure on offspring gyrification patterns and mood dysregulation in young adulthood. Participants included 85 young adults (56.5% women; 23-24 years) from the European Longitudinal Study of Pregnancy and Childhood (ELSPAC) with perinatal stress data across four distinct timepoints and structural MRI data from young adulthood. Perinatal stress exposure was measured as maternal stress during first and second half of pregnancy, first 6 months, and 6-18 months after birth. Cortical gyrification and mood dysregulation were quantified using local gyrification index (LGI), computed with Freesurfer, and the Profile of Mood States questionnaire, respectively. Perinatal stress predicted cortical gyrification in young adulthood, and its timing influenced location, direction, and sex-specificity of effects. In particular, whereas early prenatal stress was associated with sex-dependent medium-to-large effects in large temporal, parietal, and occipital regions (f2 = 0.19-0.38, p < .001), later perinatal stress was associated with sex-independent small-to-medium effects in smaller, more anterior regions (f2 = 0.10-0.19, p < .003). Moreover, in females, early prenatal stress predicted higher LGI in a large temporal region, which was further associated with mood disturbance in adulthood (r = 0.399, p = .006). These findings point out the long-term implications of perinatal stress exposure for cortical morphology and mood dysregulation.
Keywords: Young Adult; Prenatal Exposure Delayed Effects; young adulthood; Male; longitudinální studie; perinatal stress; Affective Symptoms; zpožděný efekt prenatální expozice; magnetická rezonanční tomografie; mladý dospělý; prenatal birth cohort; Infant; dysregulated mood; psychický stres; Pregnancy; těhotenství; mozková kůra; Adult; emoční regulace; dospělí; mužské pohlaví; afektivní symptomy; Emotional Regulation; sex; novorozenec; Postpartum Period; lidé; gyrification; ženské pohlaví; Humans; Stress, Psychological; magnetic resonance imaging; Infant, Newborn; kojenec; poporodní období; Longitudinal Studies; Magnetic Resonance Imaging; Female; Cerebral Cortex